Design anthropology : object culture in the 21st century. - Clarke, Alison J., ....- (Wien : Springer, 2011)
Design Anthropology brings together a unique range of cutting-edge design theorists and social scientists to explore the changing object culture of the 21st century. Decades ago, product designers utilised basic market research to fine-tune their designs for consumer success today the design process has been radically transformed; the user is now centre-stage in the design process. From design ethnography to cultural probing, innovative designers in the 21st century are relying on anthropological methods to illicit the meaning, rather than the mere form and function of stuff.The work offers the definitive guide to the issues facing the shapers of our increasingly complex material world. How has user-experience transformed our understanding of design? And how do leading design corporations, from IDEO to INTEL, harness the insight of anthropologists in generating future visions? Why are new disciplines, like digital anthropology, shaping our increasingly de-materialised product cultures?